Aplikasi Silase Limbah Sayuran Sebagai Sumber Pakan Alternatif dalam Upaya untuk Meningkatkan Persentase Karkas Entog (Cairina moschata) Jantan - Kiki Abdul Kodir; Oki Imanudin; Rachmat Somanjaya (Study Program of Animal Husbandry, Faculty of Agricultural, Universitas Majalengka, 2023)
Carcass percentage can be affected by feed consumed, age, sex, and environment. The purpose of this study was to analyze the effect of giving vegetable waste silage in the ration on the percentage of carcasses, and to obtain the optimum percentage of male musk carcass feed formulations. The research was carried out experimentally using a completely randomized design (CRD). A total of 80 male mussels were placed in 20 cage plots, so that each cage plot consisted of 4 individuals. The type of treatment used was R0 (100% rice bran) as control, R1 (75% rice bran + 25% vegetable waste silage), R2 (50% rice bran + 50% vegetable waste silage), R3 (25% rice bran + 75% vegetable waste silage). Variables observed included live weight, carcass weight, carcass percentage and carcass percentage (breast, thigh, back and wings). The research data were analyzed using analysis of variance and if they showed significant differences then further tested using Duncan's multiple range test. The results showed that the use of vegetable waste silage feed had no significant effect on carcass weight (p>0,05). However, vegetable waste silage can be used as additional feed for rice brand not lass than 25% and not more than 50%. The results showed that treatment R1 (75% rice bran + 25% vegetable waste silage) and R2 treatment (50% rice bran + 50% vegetable waste silage) produced good carcass and percentage carcass weight in male ducks.